POWER LOSSES ASSESSMENT IN TRANSFORMERS AFTER THE NORMATIVE OPERATING PERIOD - M. I. Fursanov; N. S. Petrashevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The capacity losses values both loading and off-load are topmost parameters characterizing the distribution mains customers’ transformers operating effectiveness. Precise determination of the specified values facilitates substantiated choice of the optimizing procedures. The actuality of the given topic increases owing to the fact that the modern electric grid utilizes plenty of the oil-transformers whose time in commission considerably exceeds the statutory 25 years. Under the conditions of continued operation the power-losses measurement according to the functioning guidelines does not seem always possible.The authors present an improved power-losses assessment technique based on the currently accepted thermal model of the oil-transformer. They indicate the deficiency of the existing technique and substantiate some of the changes in practical application of the mathematical model. The article makes an emphasis on peculiarities of the temperature changes in the oil-transformer and offers a prototype device of open architecture for realizing the improved technique of the power-losses measurement. The paper describes the device design features and functionality options and depicts its sketchy schematic. The authors note the potential of additional to assessing the power-losses volume, transmitting the obtained information to the dispatcher  via  GSM-connection  for  simplification  of  the  transformer  status  monitoring; as well as the capability of integrating the device into the system of the transformer thermal protection. The practical merit and application scope of the obtained results are in development and choice of the optimizing measures to be taken in the distributive electrical grids, e. g. the transformer replacement.